THE EFFECT OF TEACHER SELF-EFFICACY TOWARD ENGLISH LEARNING ACHIEVEMENT THROUGH MOTIVATION AS A MODERATOR VARIABLE - Damayanti, Adelia Shovi; Musafik, Mohammad Naim (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2022)
In this study, the results of this research to analysis the effect of each variable. There are; (1) to analysis the significant effect of teacher self-efficacy toward English learning achievement, (2) to analysis the significant effect of motivation toward English learning achievement, (3) to analysis the significant effect of teacher self-efficacy toward motivation, (4) to analysis the significant effect of teacher self-efficacy toward English learning achievement through motivation. The results of this study (1) Teacher Self-Efficacy has no significant effect toward English Learning Achievement. (2) Motivation has significant effect toward English Learning Achievement. (3) Teacher Self-Efficacy has significant effect toward Motivation. And the last (4) Teacher Self-Efficacy toward English Learning Achievement through. Motivation has significant effect indirectly. The analysis of this study used descriptive quantitative approach as a research design. In this research questionnaire was used as a data collection instrument. The use of this questionnaire was intended to measure the variable (X1) teacher self-efficacy with a total of 16 questions in the form of statements, (X2) motivation with 15 questions in the form of statements and variable (Y) English learning achievement with a total of 15 questions in the form of statements. Using Google Form to find the significant effect of teacher self-efficacy toward English learning achievement through motivation as a moderator variable. In this study, researchers used a sample of 11th grade students of SMA Negeri 7 Kediri to determine the effect of each variable to be studied. The total population of grade 11 students is 392, so that from the total number of students, 198 students will be taken by random sampling.